Descriptions of three new Pseudolitochira Ward, 1942 species (Crustacea: Brachyura: Pilumnidae) from the West Pacific. Issue 5 (16th February 2022) - Ng, Peter K.L.; Clark, Paul F.
ABSTRACT: Pseudolitochira Ward, 1942 (Brachyura: Pilumnidae) is superficially similar to Heteropilumnus De Man, 1895, but it can be distinguished from the latter by possessing a more subovate carapace, the dorsal surface of the carapace almost devoid of regions, a proportionately wider front with short anterolateral margins, and, most significantly, a different posterior margin of the epistome. In Heteropilumnus species, and most Pilumnus species, each lateral margin of the posterior margin of the epistome is separated into two parts, demarcated by a clear median fissure. In Pseudolitochira, the lateral margin is entire and evenly concave, without any trace of a cleft or fissure. For the present study, Japanese specimens reported as ' P. integra ' by Maenosono (2019) were examined and it was found that they should be referred to a new species. Furthermore, Papua New Guinea and Vanuatu specimens belong to two other new species. The present paper provides a diagnosis for the three new species and compares them with P. integra (Miers, 1884) s. str. http://www.zoobank.org/urn:lsid:zoobank.org:pub:92667FD7-735A-4430-86EC-48821DB90FB7